Oxytocin in the medial prefrontal cortex regulates maternal care, maternal aggression and anxiety during the postpartum period - Sabihi, Sara; Dong, Shirley M.; Durosko, Nicole E.; Leuner, Benedetta (Frontiers in Behavioral Neuroscience, 2014)
The neuropeptide oxytocin (OT) acts on a widespread network of brain regions to regulate numerous behavioral adaptations during the postpartum period including maternal care, maternal aggression, and anxiolysis. In the present study, we examined whether this network also includes the medial prefrontal cortex (mPFC). We found that bilateral infusion of a highly specific oxytocin receptor antagonist (OTR-A) into the prelimbic (PL) region of the mPFC increased anxiety-like behavior in postpartum, but not virgin, females. In addition, OTR blockade in the postpartum mPFC impaired maternal care behaviors and enhanced maternal aggression. Overall, these results suggest that OT in the mPFC modulates maternal care and aggression, as well as anxiety-like behavior, during the postpartum period. Although the relationship among these behaviors is complicated and further investigation is required to refine our understanding of OT actions in the maternal mPFC, these data nonetheless provide new insights into neural circuitry of OT-mediated postpartum behaviors.